Africa’s Digital Transformation and its Governance: The Long View - Karuri-Sebina, Geci; Ochara, Nixon Muganda (LUP and African Minds., 2026)
This introductory chapter sets the stage for an exploration of Africa's digital transformation and its governance. It synthesizes existing research, highlighting the challenges and opportunities within the continent's unique socio-economic and political contexts, conceptualizing digital transformation from both exogenous and endogenous perspectives. It frames key questions for Africa’s digital future, and outlines the contributions of the subsequent chapters in addressing critical dimensions of digital governance, economy, society, and the role of artificial intelligence in achieving Sustainable Development Goals. This chapter aims to foster a critical engagement with Africa's imperative to respond responsibly and boldly to these evolving digital conditions.
Keywords: Digital Transformation; Digital Governance; Digital Economy; Digital Society; Artificial Intelligence; Sustainable Development Goals; SDG-16: Peace, justice and strong institutions; SDG-9: Industry, innovation and infrastructure